Structure and Bonding of Some Newly Syntheisised Complexes of Lanthanide(III) Complexes of 4[N-(p-dimethylaminobenzalidene) Amino] Antipyrine Thiosemicarbazone - Singh, Lakshman; Sharma, Alok; Sindhu, S.K. (Asian Journal of Chemistry, 2010)
A series of complexes of the type LnX3·2(DABAAPTS), where Ln =La, Pr, Nd, Sm, Gd, Tg, Dy and Ho, X = ClO–4, or NCS–, DABAAPTS= 4[N-(p-dimethylaminobenzalidene) amino] antipyrine thiosemicarbazone have been synthesized and characterized on the basis of elemental analysis, molecular weight measurements, molar conductance, room temperature magnetic moment, infrared and electronic spectral data. The ligand DABAAPTS behaves as neutral tridentate (N2S) ligand.